The precautionary principle in public health emergency regime: Ethical and legal examinations of Vietnamese and global response to COVID-19 - Doan, Hai (Bioethics, 2024)
Responses to the COVID-19 pandemic have been widely criticized for being too delayed and indecisive. As a result, the precautionary principle has been endorsed, applauded, and proposed to guide future responses to global public health emergencies. Drawing from controversial issues in response to COVID-19, especially in Vietnam, this paper critically discusses some key ethical and legal issues of employing the precautionary principle in public health emergencies. Engaging with discussions concerning this principle, especially in environmental law where the precautionary principle first appeared as a guiding principle with objective content(s), this paper formulates the precautionary principle as ‘in dubio pro salus’, which is about advising, justifying and demanding states to proactively prepare for scenarios arising out of any public health emergency. It distinguishes the precautionary principle into moderate and hard versions. A moderate version largely takes a holistic approach and fulfils a series of criteria specified in this paper, while a hard version either permits restrictive measures to be deployed primarily on a hypothetic basis or expresses an instrumental mentality. The hard version should be rejected because of the ethical and legal problems it raises, including risk-risk tradeoffs, internal paradoxes, unjustified causing of fear and unreasonable presupposition. Ultimately, this paper defends the moderate version.